Endophyte-infected, tall fescue hay utilization by exercised, yearling horses - J.S. Pendergraft; M.J. Arns; R.H. Raub; K.K. Bolsen; F.K. Brazle (Kansas Agricultural Experiment Station Research Reports, 1993)
Fescue toxicity causes substantial production losses in sheep, cattle, and horses. These losses are attributed to an endophyte, Acremonium coenophialum. However, our results indicate that Quarter horse yearlings can be fed endophyte-infected tall fescue hay for at least 106 days with no detrimental effects on either growth or exercise performance. However, these findings have not been substantiated in other classes of horses or in horses consuming endophyte-infected fescue for longer durations.
Keywords: Cattlemen' s Day; 1993; Kansas Agricultural Experiment Station contribution; no. 93-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 678; Beef; Tall fescue; Endophyte; Yearling horses; Exercise